Building telephony systems with Asterisk : an easy introduction to using and configuring Asterisk to build feature-rich telephony systems for small and medium businesses /: an easy introduction to using and configuring Asterisk to build feature-rich telephony systems for small and medium businesses. (©2005) - Unknown
No abstract available